EXTENDED DETERRENCE: A VIEW FROM IRAN - Janković, Slobodan (National interest, 2024)
Extended deterrence is part of the strategy aimed at dissuading the rival or enemy from armed actions against allies and therefore against the country preparing the deterrence itself. Iran as a regional power has built a partnership with several Middle East actors and a diplomatic alliance with several out of region countries, in particular with Russia and China. Thus, what might be called Iranian extended deterrence, toward USA and Israel functions regionally and globally and has diplomatic, and armed dimension. The concept of extended deterrence in the case of Iran it is not functioning as the country applies macro deterrence. It is a strategy of using multiple, state and non-state actors, military and diplomatic efforts to further away the threat of direct military aggression and to broaden the front of resistance to threats. Combination of this concept and of the strategic patience contributed to the postponement of the attacks, also on allies.  Author presented adaptation of Iranian strategic thinking based on historical experience, context and ideology of Islamic Revolution, for which defensive strategies and asymmetric hybrid warfare are characteristic of Iranian approach toward enemies and rivals.
Keywords: Iran; deterrence; Middle East; Hezbollah; Israel; Iraq; Lebanon